Learning Analysis of the Qira'ati Method in Al-Qur'an Learning Activities - Yuyun Bahtiar; Aprilia Salsa Nabila; Nurul Afidah; Hanifah (SCHOOLAR: Social and Literature Study in Education, 2023)
This study aims to determine the learning system of the Qira'ati method in learning the Al-Qur'an at TPQ Mathlabul Huda Paciran Lamongan and to find out the obstacles encountered in learning the Qira'ati method in learning the Qu’ran at TPQ Mathlabul Huda Paciran Lamongan. This research is qualitative in nature, taking the background of TPQ Mathlabul Huda Paciran Lamongan. Where researchers go to the field to make direct observations about a phenomenon that occurs. By using a theoretical basis that is used as a guide so that the research focus is in accordance with the facts in the field. Data collection techniques were carried out through interviews, observation, and documentation. The results of the study show that the Ustadzah has implemented the Qira'ati learning system in learning the Qur'an very well. moreover, it is accompanied by an introductory book to learning the Al-Qur'an for students. Very good learning in terms of knowing hijaiyah letters, reading ghorib musykilat, understanding tajwid material, and reading the Al-Qur'an. The obstacle encountered during the implementation of the Qira'ati method was that there were some students who were late for the activity.